Testing the impact of oceanic barriers on population subdivision, speciation and zoogeographical community assembly in Xylotrupes beetles across the Indo-Australian Archipelago. (30th July 2018) - Huang, Jen-Pan; Knowles, L Lacey
Abstract: Whether the impact of a specific barrier type is consistent across multiple levels of biodiversity (e.g. populations vs. species) and whether phylogeographical and biogeographical patterns can be structured by the same isolation force have rarely been investigated in evolutionary studies. We investigated the effect of oceanic barriers on genetic divergence among Xylotrupes beetles from the Indo-Australian Archipelago. We found that zoogeographical regions isolated by oceanic trenches were characterized by endemic lineages/species complexes. Dispersal was rare between regions. We further found that populations separated by oceanic barriers were associated with a significantly higher population subdivision compared with populations not separated by oceanic barriers. We did not, however, detect an increased rate of speciation associated with oceanic barriers, implying that the impact of oceanic barriers on population- vs. species-level genetic divergence may have differed. Although our simulation results suggest limited statistical power for detecting concerted divergence, we hypothesize that the concerted action of a barrier at different levels of biodiversity may depend on the mediating effects of the diversification process itself, such as the duration of speciation and the time required for sympatric species to evolve coexistence.